Terminal myeloid differentiation in vivo is induced by FLT3 inhibition in FLT3/ITD AML - Sexauer, Amy (American Society of Hematology, 2012)
A hallmark of cancer is the disruption of differentiation within tumor cells. Internal tandem duplication mutations of the FLT3 kinase (FLT3/ITD) occur commonly in acute myeloid leukemia (AML) and are associated with poor survival, leading to efforts to develop FLT3 kinase inhibitors. However, FLT3 inhibitors have thus far met with limited success, inducing only a clearance of peripheral blasts with minimal BM responses. Quizartinib is a novel potent and selective FLT3 inhibitor currently being studied in clinical trials. In 13 of 14 FLT3/ITD AML patients with normal karyotype treated with quizartinib, we observed terminal myeloid differentiation of BM blasts in association with a clinical differentiation syndrome. The single patient whose blasts failed to differentiate had a preexisting C/EBPα mutation and another developed a C/EBPα mutation at disease progression, suggesting a mechanism of resistance to FLT3 inhibition. In vitro, in primary blasts cocultured with human BM stroma, FLT3 inhibition with quizartinib induced cell-cycle arrest and differentiation rather than apoptosis. The present study is the first description of terminal differentiation of cancer cells in patients treated with a tyrosine kinase inhibitor. These data highlight the importance of the differentiation block in the patho-genesis of AML.